Denial Verbal Actions in Surah in Al-A’raf - Mohammed, Abdulaziz (Humanities Journal of University of Zakho, 2022)
The concept of Verbal actions is not limited to linking and communicating concepts and information to the other side of the recipient. On the contrary, it plays a much broader and greater role, that is, it pays attention to the meaning and expressions of linguistic expressions by converting abstract and superficial words into verbal actions with intentional meanings and characteristics, whose meaning and impact on the linguistic reality appears. In addition, verbal actions are launched from a suggestive perspective, not subject to or matter to the standard of verbal theorizing only, but rather play a prominent and effective role in achieving new postures, meaning changing the state of things in the universe through the realization of an action on the ground, that is: that the performance power might be varied according to the context of the principal as well as the goals and purposes of the speaker. This study is considered a modest effort in the field of linking the Holy Qur’an with modern linguistic studies, through a Surat al-A’raf, which is one of the most comprehensive chapters of the Holy Qur’an in crystallizing denial verbal acts, from the purposes and meanings, and from a warning to the polytheists about the bad consequences of polytheism in this world and the next world. Therefore, the denial verbal acts in this Surah, specifically, came to show the extent of insistence on the ingratitude of the apostles with their people. To find out the most important communicative and scientific fields in the Holy Qur’an, through the deliberative connotation of verbal denial actions that have a close relationship with interactive purposes, templates with communicative dimensions, and linking them to divine evidence and verifications.